(untitled) ("Conference on Universal Science Research 2023", 2023)
Medicinal plants are very important today. Medicinal plants have many benefits for the human body and are safe. plant is widely used in human life and medicine. Cultivating it as a medicinal plant and increasing the planting area is an urgent problem today.